Modelling Thermomechanical Response of a Diamond Particle in a Metallic Matrix - Jan LACHOWSKI; Joanna BOROWIECKA-JAMROZEK (Engineering Transactions, 2017)
The paper deals with numerical and analytical modelling of synthetic diamond particle retention in a metallic matrix. The model of a diamond particle embedded in a metallic matrix was created using the Abaqus software. The numerical results were compared with the experimental data. The analytical model of a spherical particle in a metallic matrix was built. The analysis has indicated the mechanical parameters responsible for the retention of diamond particles in a matrix.